(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The spleen is an important organ of the immune system responsible for blood filtration, involved in the development of lymphocytes and the formation of antibodies. The main functions of the spleen in the immune response, its influence on the processes of formation and activation of immunity are analyzed. The article also presents data on the influence of the spleen on the formation of memory of the immune system and its ability to adapt to new pathogens. The study of the biological role of the spleen in the processes of immunogenesis allows us to better understand the mechanisms of functioning of the immune system and unlock the potential for developing new approaches to strengthening the immune response.